Chapter Poggio Bracciolini, Phyllis Goodhart Gordan, and the Formation of the Goodhart Collection of Fifteenth-Century Books at Bryn Mawr College - Pumroy, Eric L. (Atti, 2020)
The Poggio Bracciolini conference was dedicated to Bryn Mawr alumna Phyllis Goodhart Gordan (1913-1994) one of the leading Poggio scholars of her generation and the editor of the only major collection of Poggio's letters in English, Two Renaissance Book Hunters (Columbia University Press, 1974). Gordan and her father, Howard Lehman Goodhart (1887-1951) were also responsible for building one of the great collections of 15th century printed books in America, most of which is now at Bryn Mawr College. This paper draws upon Goodhart's correspondence with rare book dealers and the extensive notes on his books to survey the strengths of the collection and to examine the process by which he built the collection and worked with rare book dealers in the difficult Depression and World War II years, the period when he acquired most of his books. The paper also considers Goodhart's growing connections with scholars of early printing as his collection and interests grew, in particular the work of Margaret Bingham Stillwell, the editor of Incunabula in American Libraries (1940).